Protocol for efficient germination of Castilleja (Orobanchaceae) for chemical haustorium induction and parasite-host interaction studies - Sagar Bashyal; Lena Maria Müller; Joanne Chory; Marco Bürger (STAR Protocols)
Summary: We present a protocol for germinating Castilleja seeds and growing seedlings for hormone treatments and plant-plant interaction assays. We describe steps for seed sterilization, stratification, and transplantation, ensuring germination and seedling development. We detail procedures for haustorium formation, including strigolactone treatment and co-inoculation to induce root interactions with a host plant. This protocol includes optimized nutrient conditions and microscopy techniques to ensure experimental reproducibility. This approach enables reliable investigation of haustorium formation in Castilleja under laboratory conditions.For complete details on the use and execution of this protocol, please refer to Bürger et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.